The aging clock - Ateşşahin, Dilek Arslan; Durna, Yusuf Muhammed (Nova Science Publishers, Inc., 2024)
The diurnal alternation between light and darkness, constituting a roughly 24-hour cycle, exerts a significant influence on the temporal orchestration of biological processes within living organisms. These cyclic modulations, encompassing physiological, biochemical, and behavioral manifestations, are collectively recognized as circadian rhythms. Extensive empirical investigations have consistently demonstrated a progressive decline in circadian rhythms throughout the lifespan of organisms. This attenuation is intrinsically associated with genetic modifications within circadian genes and perturbations within the molecular chronometer, thus correlating these alterations with the aging phenomenon. Aging, a complex and multifaceted phenomenon, is characterized by a myriad of biological, biochemical, and physiological transformations. Several intracellular pathways have direct influence over cellular and epigenetic mechanisms that govern the aging process. It has been ascertained that certain pathways implicated in nutrient sensing concurrently participate in the regulatory processes governing aging and the molecular chronometer. Furthermore, aging is intricately intertwined with perturbations in circadian rhythms and the modulation of energy homeostasis, consequently affecting a plethora of metabolic pathways. Hence, therapeutic strategies aimed at the manipulation of circadian regulation, aging, maintenance of metabolic energy equilibrium, and nutrient sensing pathways hold substantial promise in enhancing the efficiency of interventions. In this chapter, the intricate interplay between the aging process and the circadian clock is meticulously examined and evaluated. © 2024 Nova Science Publishers, Inc. All rights reserved.
Keywords: Aging; Circadian clock; Energy balance; Gene; Metabolic pathway